Perbandingan Biaya Pengendalian Gulma pada 2 Metode Penyiraman Drip Irrigation dan Mist Irrigation di Pembibitan Main Nursery - Sinulingga, Putra Jaya; Hasibuan, Henry Budi (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study was conducted at PT Perkebunan Nusantara IV Regional 2, Adolina Plantation and the Seed Center. The study was carried out from November to December 2025. It employed a quantitative descriptive method with a comparative approach. The application of the mist irrigation method caused the area around the nursery to become damp, thereby supporting weed growth, as indicated by the relatively high number of weeds growing. In contrast, with drip irrigation, water delivery is more focused on the plant root zone, resulting in relatively low soil surface moisture. In terms of weed control costs, the drip irrigation method incurred a total cost of Rp. 1.420.000, while the mist irrigation method incurred a total cost of Rp. 1.580.000; this is due to differences in the prices of active ingredients and labor costs. This cost difference stems from the cost management plan formulated by the nursery assistant. The application of the drip irrigation method is more effective in suppressing weed growth because water delivery is focused on the root zone of the oil palm seedlings. Based on the results of the study, drip irrigation has proven to be more effective than mist irrigation in controlling weeds in the main oil palm nursery. This conclusion is based on cost, water use efficiency, and weed growth rates for each method.